Formation of the European Local Self-government Model in Ukraine: Developments and Expectations - Strutynskyi, Vladyslav; Strutynska-Struk, Liudmyla (Political Preferences, 2019)
The article examines the issues of the formation European local self-government. The analysis of the local self-government development in Ukraine is presented. The author explores the existing local self-government legal framework with regard to a possibility of applying the European experience in this sphere to the Ukrainian legislation. Special attention is paid to the existing implementation problems of the adopted laws.